Prevalence of primary dysmenorrhea in young adult female university students - Polat, Aytac; Celik, Husnu; Gurates, Bilgin; Kaya, Diren; Nalbant, Mehmet; Kavak, Ebru; Hanay, Fethi (Springer Heidelberg, 2009)
To determine the prevalence of primary dysmenorrhea and attitudes and behavior toward dysmenorrhea in the female students of an university toward this problem. A total of 1,266 female university students were anonymously surveyed by doctors. It was found that mean age of the surveyed students was 21.02 +/- A 2.13 years, mean menarche age was 13.3 +/- A 1.4 years, and menstruation frequency was 32.58 +/- A 19.8 days. Of the students, 45.3% were found to suffer pain in each menstruation, 42.5% in some and 12.2% in none. Of those with primary dysmenorrhea, 66.9% were established to take analgesic drugs. Prevalence of primary dysmenorrhea was found higher than that cited in the literature. It was established that although the rate of consultation with health professionals about menstruation and related changes was low, use of agents known to be effective in primary dysmenorrhea treatment was highly common.
Keywords: Dysmenorrhea; Menstruation; Adolescent females; Turkey